Desain Hadits Tarbawi dalam Aqidah Spritual dan Kurikulumnya - Mohd Fauzan; Husti, Ilyas; Nurhadi, Nurhadi (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to find out the spiritual aqidah curriculum and the curriculum contained in the hadith. The research method used is literature study because the research data comes from hadith books, books, journals and research results of researchers and Islamic scholars. The conclusion is; Aqidah education is an approach to religious education, meaning that the teachings of a particular religion are used as a source of inspiration to develop pedagogical theories or concepts and form spiritual aqidah education in clearly explained hadiths, namely faith in Allah SWT, faith in the angels of Allah SWT, faith in the books Allah, belief in Allah's Messengers, belief in the hereafter, belief in good and bad destiny are from Allah SWT (qada' and qadar).